Emerging & Innovative Technology Application in Libraries: Cloud Computing Services: Exploring the Application of Cloud Computing Services in Libraries (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Latest technological development has brought a dramatic change in libraries. The libraries have been automated and moving towards to virtual libraries. The profession librarians are also using different platforms in Libraries for information handling. Library automation has helped to provide easy access to collections through the use of computerized library catalogue such as On-line Public Access Catalog (OPAC). Cloud Computing helps to provide easy access of the digital resources to the patrons with retrieving facility. Cloud computing can enhance the implementation of digital Library projects by reducing the cost involved in the whole processor and to get connected with all Institutions strictly and efficiently. Cloud Computing provides real time access utilities and user pay for what they use only through various implementation models. Cloud computing offers user centered multilevel services. This paper overviews the basic concept of cloud computing. The use of cloud computing in libraries and how cloud computing actually works.